C-reactive protein in infants with no evidence of early-onset sepsis. (12th December 2022) - Rallis, Dimitrios; Balomenou, Foteini; Kappatou, Kleio; Karantanou, Konstantina; Tzoufi, Meropi; Giapros, Vasileios
Abstract: Objective: C-reactive protein (CRP) is one of the most extensively used biomarkers in the investigation of early-onset sepsis (EOS). Current evidence suggests the normal kinetics of serum CRP should be considered when evaluating infants for presumable EOS. The current study aimed to evaluate the CRP kinetics, and to establish percentiles in a cohort of term and near-term infants with no evidence of confirmed or clinical EOS. Methods: We retrospectively reviewed the medical records of all neonates ≥34 weeks' gestation screened for presumable EOS, from January until December 2019. We also recorded the clinical management, the blood culture, serial CRP, and white blood cell count analysis of each infant. All infants that received antibiotics for confirmed or presumed EOS were excluded from the analysis. Results: During the study period, 145 infants were detected; 109 (75%) term and 36 (25%) preterm. Term infants had significantly higher median values of CRP at all time points in comparison to preterm infants. Term infants presented a significant rise of CRP at 24 and 36 h, with a peak at 24 h (median 4 (range 1–12) mg/L). Preterm infants had a significant rise of CRP at 24 but not at 36 h, with a peak at 24 h (median 3 (range 1–9) mg/L). In term infants, the 90th percentile of CRP at 24 h was 10.80 mg/L and the 97th percentile was 12.00 mg/L. In preterm infants, the 90th percentile of CRP at 24 h was 7.60 mg/L and the 97th percentile was 8.00 mg/L. Conclusions: Term and near-term asymptomatic infants had a rise in CRP during the first days of life. Term infants had a more pronounced CRP response in comparison to preterm infants.